New museum theory and practice : an introduction - Marstine, Janet (Malden, MA : Blackwell, 2006)
- The architecture is the museum / Michaela Giebelhausen##- Feminist curatorial strategies and practices since the 1970s / Katy Deepwell##- New art, new challenges: the changing face of conservation in the twenty-first century / Rachel Baker and Patricia Smithen##- How we study history museums: or cultural studies at Monticello / Eric Gable##- Spectacle and democracy: experience music project as a post-museum / Chris Bruce##- Revealing and concealing: museums, objects, and the transmission of knowledge in aboriginal Australia / Moira G. Simpson##- Restructuring South African museums: reality and rhetoric within Cape Town / Julie L. McGee##- The critical museum visitor / Margaret Lindauer##- Visiting the virtual museum: art and experience online / Lianne McTavish##- Reframing studio art production and critique / Helen Klebesadel##- The university museum and gallery: a site for institutional critique and a focus of the curriculum / Lyndel King and Janet Marstine##- Museum archives as resources for scholarly research and institutional identity / Lois Marie Fink.
CCS Gent
Includes bibliographical references (p. 308-321) and index.
boek